2014
DOI: 10.7727/wimj.2012.010
|View full text |Cite
|
Sign up to set email alerts
|

Sonographic Biometry of Normal Kidney Dimensions among School-age Children in Nsukka, Southeast, Nigeria

Abstract: Background: Some kidney diseases are usually associated with changes in kidney size. Objective: To determine sonographically the normal limits and percentile curves of the kidney dimensions according to age, gender and somatometric parameters among school-age children. Methods: A prospective cross-sectional research design and convenience sampling method were utilized. Participants included 947 normal subjects (496 boys and 451 girls) aged 6−17 years old. The sonographic examination was performed on a Shenzhen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
9
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 0 publications
2
9
0
1
Order By: Relevance
“…It was shown that there was no correlation between renal length and body weight of the individual and also no relation between BMI [32]. Thus these observations were in agreement with the studies conducted by Eze, et al [29] and Younus et al [31] 50 obese and 50 non-obese children and adolescent aged 1-19 years were included in a study for estimation of relationship between renal length and body mass index (BMI) by Soheilipour, et al [2] 100 children and adolescent were screened ultrasonographycally and the longest longitudinal measurement in deep inspiration was taken as the kidney length. Mean height of the control group was (144.44 ± 23) cm and for obese group was (145.9 ± 22.05) cm.…”
Section: Bmi Influencing Renal Lengthsupporting
confidence: 91%
See 3 more Smart Citations
“…It was shown that there was no correlation between renal length and body weight of the individual and also no relation between BMI [32]. Thus these observations were in agreement with the studies conducted by Eze, et al [29] and Younus et al [31] 50 obese and 50 non-obese children and adolescent aged 1-19 years were included in a study for estimation of relationship between renal length and body mass index (BMI) by Soheilipour, et al [2] 100 children and adolescent were screened ultrasonographycally and the longest longitudinal measurement in deep inspiration was taken as the kidney length. Mean height of the control group was (144.44 ± 23) cm and for obese group was (145.9 ± 22.05) cm.…”
Section: Bmi Influencing Renal Lengthsupporting
confidence: 91%
“…Anthropometric measurements like height, weight, abdominal circumference and body mass index (BMI) were also recorded. In this study, authors had established prediction models of the kidney lengths of corresponding side in millimeters according to BMI and these are: a) Left kidney length=0.01×child BMI+6.72, r ² =0.05 b) Right kidney length=0.08×child BMI+6.72, r ² =0.13 [28] Eze et al [29] estimated kidney dimensions among 947 apparently healthy school age children using sonography. Kidney dimensions obtained in coronal plane passing through the renal hilum, three times and the mean values were recorded.…”
Section: Bmi Influencing Renal Lengthmentioning
confidence: 99%
See 2 more Smart Citations
“…Serial volume measurements can be used to track the normal growth pattern of kidneys and to follow the known pathology of kidney in children. The establishment of normal kidney values in routine imaging tests can serve as a baseline for the diagnosis of kidney disease associated with changes in size, such as acute or chronic pyelonephritis (4) . There are several methods for measuring renal sizes, including abdominal CT and MRI.…”
Section: Introductionmentioning
confidence: 99%